Situando a África Ocidental pré-colonial na história econômica global - Warchol, Abigail (Afro-Ásia, 2021)
Resenha de: GREEN, Toby. A Fistful of Shells: West Africa from the Rise of the Slave Trade to the Age of Revolutions. Chicago: University of Chicago Press, 2019. 614p.